Efectos remineralizantes de extractos y fracciones de especies vegetales, sobre el esmalte dental, en estudios in vitro: Una revisión sistemática (2021)
The white spot produced on dental enamel is a common event during dental practice and especially in orthodontic practice; for your control is Self-care and a balanced diet are important, contributing to the use of products that control demineralization, such as natural products which show promising results in this area.